Thrombolytic therapy for acute stroke - Lyden, Patrick D. (Berlin : Springer, 2015)
Thrombolytic therapy is now reaching patients in a variety of settings all over the world. Formerly in the domain of sub-specialists, thrombolytic therapy now rests in the realm of emergency medicine, intensive care, vascular, and neurocritical physicians. Extensively updated from previous editions, Thrombolytic Therapy for Acute Stroke, Third Edition is a practical and thorough reference to all those caring for acute stroke patients. Chapters feature new data, technologies and cases offering guidance to treating acute stroke patients ? with or without thrombolytic therapy. Physicians looking to utilize thrombolytic therapy for acute stroke will find this text an invaluable resource
Mechanisms of Thrombolysis -- The Ischemic Penumbra and Cell Survival -- The March of Thrombolytic Therapy for Acute Ischemic Stroke to Clinical Trials: Pre-Clinical Thrombolysis and Adjuncts to Thrombolysis Research -- Combination of Thrombolytic Therapy with Antithrombotics and Neuroprotectants -- Pilot and Preliminary Studies of Thrombolytic Therapy for Stroke -- Intravenous Thrombolytic Therapy for Acute Ischemic Stroke: Results of Large, Randomized Clinical Trials -- Intra-Arterial Thrombolysis in Acute Ischemic Stroke -- Mechanical Revascularization with Embolectomy Devices -- Combinations of Intravenous t-PA and Endovascular Therapy -- Thrombolytic Therapy for Acute Stroke and the Test of Time -- How to Run an Effective Code Stroke -- Telestroke: Delivery and Design -- The Impact of Neuroimaging on Acute Stroke Treatment: Role of Magnetic Resonance Imaging -- The rt-PA for Acute Stroke Protocol
Includes bibliographical references
1 13
Keywords: Cerebrovascular disease; Thrombolytic therapy; Electronic books